ORGANISATIONAL AND ECONOMIC MECHANISM FOR THE INTRODUCTION OF CRITICAL TECHNOLOGIES IN THE ENERGY SECTOR (INNOVATIVE ECONOMY, 2023)
Putsenteilo P.R., Brych V.Ya., Hunko S.I. ORGANISATIONAL AND ECONOMIC MECHANISM FOR THE INTRODUCTION OF CRITICAL TECHNOLOGIES IN THE ENERGY SECTORPurpose. The aim of the article is to study the state and substantiate the proposals for the development of an organizational and economic mechanism for ensuring the development of critical technologies in the energy sector.Methodology of research. The dialectical method of scientific knowledge is the methodological basis of research. General scientific and special methods were used in the research process, in particular: analysis and synthesis, dialectical – to determine the initial conditions and content of critical technologies; analytical – when processing literary and Internet sources on the content of critical technologies in the energy sector; cause and effect – to determine the postulates of the development of the energy sector of Ukraine; abstract and logical – for outlining the main directions of functioning of critical technologies in the field of energy, forming conclusions and proposals; visual and schematic – for publicizing creative searches for the development of the energy sector of Ukraine.Findings. Current and prospective critical technologies in the energy sector, which will be able to ensure the growth of efficiency of the energy sector of Ukraine, are summarized. The content is clarified, the characteristic features are revealed, and the priority directions for the development of critical technologies are highlighted. The list of promising energy technologies in the field of energy of Ukraine is substantiated.It was determined that an effective mechanism of interaction between the state and business in the energy sector can be organizational and innovative support for the creation and development of critical technologies based on the energy clustering of the national economy. This mechanism should be aimed at the development and implementation of critical technologies that will allow the sustainable and efficient operation of the energy sector and ensure the energy security of the country. The principles of management of critical technologies in the field of energy are substantiated.Originality. Assumptions regarding the need to improve the organizational mechanism for managing innovative activities for the development and support of critical technologies in the energy sector on the basis of energy clustering of the national economy are made in the article. An attempt is made to create a road map for the development and introduction of critical technologies in the energy sector.Practical value. The substantiated research results can be used to develop proposals for improving the organizational and economic mechanism for ensuring the development of critical technologies in the energy sector.Key words: energy, energy sector, critical technologies, innovations, organizational and economic mechanism, road map.
Keywords: energy; energy sector; critical technologies; innovations; organizational and economic mechanism; road map.